PENERAPAN LOGIKA FUZZY DALAM OPTIMASI PRODUKSI BARANG MENGGUNAKAN METODE MAMDANI - Priyo, Wahyu Toto (Universitas Dr. Soetomo, 2017)
Developement and revolution of the era are always followed by the development of technology and sciences. Along with the development of the era, it will be found various problems in various aspects of life, including in the field of industry. Often companies experience obstacles in meeting the number of requests from consumers, or even the amount of inventory of many goods. From these problems required an appropriate solution for production problems can be resolved. In this research, we will apply Fuzzy Logic as one of alternative solution of goods production problem, that is by using Mamdani method, with the quantity of demand and inventory of goods as input variable and quantity of goods produced as output variable. Then followed by 4 stages, namely: (a) Formation of fuzzy set by fuzzification process, (b) Application of implication function, (c) Composition of rules with maximum method, (d) Process defuzzification with centroid method that will result outout amount of goods which must be produced by the company. From the results of the analysis that has been done, by entering the input variables the number of requests amounted to 54,900 units and the amount of inventory amounted to 4060 units produce output production amounted to 46,600 units. Keywords: Fuzzy Logic, Mamdani methode, goods production